Social and economic interjacent process in the logical discourse of synergetics - Popov, Vitaly V.; Muzika, Oksana A.; Kobysheva, Larisa I.; Kozenko, Yana V.; Pashkovsky, Pavel V.; Paronyan, Karen M. (International Journal of Psychosocial Rehabilitation, 2020)
This article considers the methodological approaches to modern society undergoing social and economic transformations. Authors have shown the existance of analysis challenges of the interjacent process, which, subsequently, implies its investigation and presentation with further consideration of axiological, praxeological, and methodological aspects. We have demonstrated that if the discourse involves talking about the internal structure of the interjacent process from authoritarianism to democracy itself, there is a point to say there are various options of exiting from the transition periods that are characteristics of such social and economic development structure. It was shown that phenomenological gaps can be mitigated with the problems that arise when certain connections are not yet established between dynamic categories, when there is no correlation between the terms that have to not only depict transformations and movements of development and formation but also be in a certain system.